Integrating Siskeudes, Internal Control and Competence in Enhancing Village Financial Governance - Vidya Vitta Adhivinna; Ratna Purnama Sari; Jatmiko Aji Nugroho (GOVERNORS, 2025)
This study employs a quantitative research design using primary survey data to analyze how the implementation of the village financial system, internal control effectiveness, and village officials’ competence affect the quality of village financial management in Kaligesing District, Purworejo Regency. A purposive sampling technique produced 120 respondents from village apparatus, and the data were analyzed using multiple linear regression. The results show that the village financial system, internal control, and officials’ competence each have a positive and statistically significant effect on village financial management performance. Empirically, these findings demonstrate that digital accounting systems alone are not sufficient; they must be embedded in effective control structures and supported by competent apparatus to improve accountability, transparency, and financial performance at the village level. Theoretically, this study extends governance and public sector accounting literature by providing village-level evidence on how information systems, internal control mechanisms, and human resource capabilities jointly shape financial governance outcomes within a stewardship-based perspective. Practically, the results offer guidance for regulators and local governments in designing integrated interventions that combine system enhancement, internal control strengthening, and continuous capacity building for village officials to promote more transparent and accountable village financial management.